Relationship between maternal education and socioeconomic status on knowledge, attitude and practice of mother and her child regarding acute diarrhoeal diseases - Mutalik, Anirudh V.; Raje, Vaishali V. (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, diarrhoea caused more than 130,000 child deaths in 2013. This also accounts for roughly one-fourth of all global diarrhoea deaths among children under five years of age. The incidence of diarrhoeal disease in rural India is 12% and in urban India is 9%.Acute diarrheal disease is both preventable and treatable. Untreated severe diarrhoea leads to fluid loss and it may be life-threatening especially in young children and among the people who are high risk like malnourished or have impaired immunity. Methods: A cross sectional study was carried out among the secondary high school children (8th std) Azad high school, Kasegaon to find out the relationship between maternal education and socioeconomic status on knowledge, attitude and practice of mother and her child regarding acute diarrhoeal diseases. A pre-structured and pretested questionnaire was used to get the information regarding definition, causes, signs, symptoms, treatment, preparation of ORS, prevention of diarrheal etc. Results: Nearly 57% of the mothers had school education and 10% had college education and illiteracy was 36%. As per the occupation 46.6% were farmers, 30.6% were labours and 14% were housewives. Mother’s education was significantly associated with children Knowledge, attitude whereas practice was not associated. Illiterate mothers had significant poor knowledge and attitude. Conclusions: Maternal education and maternal socio economic status has important role is ascertaining the knowledge, attitude and practice of her children regarding acute diarrhoeal diseases.